The diagnostic challenge of type 3 Brugada pattern: clinical implications and provocative testing strategies - Rojo, Pedro Luis Matus; Lopez, Donaldo Emiliano Silva; Andrade, Héctor Daniel Zamora; López, Pedro Emmanuel Escárzaga; Mascareño, Celina Guadalupe Camacho; Soto, Erick Adolfo Meza (International Journal of Research in Medical Sciences, 2025)
The Brugada syndrome (BrS) is a channelopathy associated with an increased risk of sudden cardiac death (SCD), characterized by distinctive electrocardiographic (ECG) patterns. While type 1 Brugada pattern is diagnostic, type 2 and 3 patterns are non-diagnostic and require further evaluation. The type 3 Brugada pattern, characterized by a <2 mm saddleback ST-segment elevation followed by a positive T-wave, poses significant diagnostic uncertainty due to its dynamic nature and overlap with benign ECG variants. Provocative testing with sodium channel blockers (e.g., ajmaline, flecainide, or procainamide) is often necessary to unmask a diagnostic type 1 pattern. However, the indications, timing, and safety of pharmacological challenge remain debated, particularly in asymptomatic individuals or those with low pretest probability. This review explores the diagnostic dilemmas of type 3 Brugada pattern, analyzes risk stratification criteria, and provides evidence-based recommendations on when to perform provocative testing. Key considerations include clinical history, family history of SCD, syncope of unknown origin, and the presence of arrhythmic symptoms. A structured diagnostic approach is essential to avoid both underdiagnosis and overmedicalization in this clinically ambiguous population.